Analisis Filosofis Pendidikan Karakter Menurut Ibnu Maskawaih - Heryana Nugraha; Irawan Irawan; Tedi Priatna (Journal on Education, 2024)
The aim of this research is to philosophically analyze character education expressed by Ibnu Maskawaih in the book "Tahdzibul Akhlak". Ibnu Miskawih is a figure in Islamic philosophy who has thoughts about character education in his book Tahdzib Al-Akhlak which consists of four steps, namely self-restraint, courage, wisdom and justice. This research uses a qualitative approach with descriptive methods, using technical content analysis of various documents as primary and secondary sources. The conclusion is that Ibnu Maskawaih belongs to the active dualist school which believes that human character is influenced by the environment which will support the goals of character education to achieve virtue and happiness.